Prenatal Ozone Exposure Induces Memory Deficiencies in Newborns Rats - Custodio, Verónica; Rubio, Carmen; Paz, Carlos (Frontiers in Molecular Neuroscience, 2019)
SUMMARY Air pollution is fully acknowledged to represent a major public health issue. Toxic environmental substances, such as ozone, interfere with prenatal development. Animals exposed to ozone (O3) in-utero develop biochemical and morphological alterations. This gas has been proven to decrease cognitive capacity in different species. In the present study, we assessed the possible alterations in memory and spatial learning in the offspring of female rats who were exposed to 1.0 ppm of O3 embryonic development. Two instruments were used to evaluate possible alterations: the T-maze and a Skinner box. MAPK, ERK, pERK and NR2B proteins, which are widely regarded as responsible for the learning process in the hippocampus and cortex, were also assessed by immunohistochemistry. We found that male rats exposed to O3 in-utero displayed a significant delay to reach the correct response using the spatial learning test as compared to the control group. The female rats exposed to O3 showed a significant delay to reach the correct response as compared to the female control group in the Skinner box. We also found that while the male rats showed decrease in significant differences in the expression of NR2B, ERK and increase in MAPK. Females only showed increase in MAPK, p-ERK and decrease in ERK, when compared to their respective control group. It is possible that the deficits are associated to hormonal expression, inflammation and oxidative stress alterations. In summary, these results suggest that exposure to O3 can interfere with prenatal development, resulting in learning and memory deficiencies in rats.